Improving Energy Efficiency in Ammonia Production from Hydrogen and Nitrogen Through Optimizing Operating Condition - Daffa Pratama Ramadhan; Fransiska Klarisa Teodora Hutasoit; Ghazy Arya Primaditya; Muhammad Verrel Aurielly; Muhammad Yusuf Zachraey Muafi (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
As a key raw material in the fertilizer industry, global ammonia consumption showed a steady increase from 2010 to 2020, with an average annual growth rate of approximately 1.81%. The production of ammonia involves four primary stages: feed gas pre-treatment, syngas generation, syngas purification, and ammonia synthesis. The main feedstocks used in this process are natural gas, steam, and air. To accommodate the rising demand for ammonia, it is essential to implement a highly efficient production process that ensures a high conversion rate. One strategy to enhance efficiency involves reducing the operating pressure in the ammonia production process proves to be an effective strategy for enhancing overall energy efficiency. This adjustment lowers the compressor workload, which in turn reduces system temperatures and eases the demand on the cooling system. Importantly, the process maintains a gas-phase reaction environment and high conversion efficiency, indicating that energy savings are achieved without compromising reaction performance. The results confirm that pressure optimization lies within the thermodynamic and kinetic boundaries necessary for effective ammonia synthesis. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).